Influence of Fluctuation in Supply Pressure on the Elastohydrodynamic Lubrication（EHL） of Water-lubricated Hybrid Journal Bearing - Zhang Tonggang; Wang Youqiang; Xu Caihong; Wang Limei (Jixie chuandong)
The model of water- lubricated hybrid journal bearings is established. The elastohydrodynamic lubrication of water- lubricated hybrid journal bearings are investigated with considering the fluctuation of supply pressure which due to the instability of throttling devices. The influence of film pressure and thickness of water- lubricated hybrid journal bearings caused by different forms of fluctuation in supply pressure is compared. The influence of elastohydrodynamic lubrication caused by load and entrainment velocity under fluctuation of supply pressure is analyzed,and the control basis supply pressure under different working conditions is obtained. The results show that the fluctuation trend of the supply pressure is the same as that of the film thickness and is opposite to that of the lubricating film pressure and the pressure fluctuation is not conducive to bearing lubrication. The larger entrainment velocity and the smaller load are helpful to relieve the damage caused by the supply pressure fluctuation to the lubrication. The basis of the fluctuation range of supply pressure under different working conditions is approximate obtained.